DETERMINATION OF SUICIDE BEHAVIOR OF MINORS - Sysoieva, Viktoriia; Osadchenko, Iryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: to analyze the suicidal behavior of minors and study the phenomenon of suicidal behavior through the prism of various factors. The methodological basis: тhe research was conducted using the dialectical method of analysis and synthesis, the method of cognition, abstraction, general scientific and special legal research methods. Results: the author outlines the determinants of juvenile suicide and emphasizes the need for preventive measures with adolescents. Discussion: the article considers specific components of preventive work with minors. If we consider adolescent suicidal behavior, we can distinguish its characteristic features: indifference, anger, apathy, which can be manifested in sarcastic statements, hypersensitivity, low self-esteem, frustration in people, including friends, the desire to be independent and independent. expectation of sincere patronage of parents, teachers, experiencing their uselessness, futility, meaninglessness of life. The first thing you need to pay attention to is the psychological education of teachers, parents and children. This can be achieved by creating an information corner in the school, which will house methodological literature, a hotline, data on psychological care centers and other professionals. Psychological and pedagogical seminars, colloquia, master classes with the invitation of specialists should be held in schools, which will cover issues of emotional disorders in children and adolescents, factors influencing the suicidal behavior of minors, the value of personality. The second thing to emphasize is the creation of a positive psychological climate in the school and family, involving students in social activities, activities (sports, clubs), cultural events that serve to create positive feelings of minors. This type of work is implemented in consultation with students, their parents and teachers. It is also necessary to constantly monitor the signs, trends, risks of suicidal behavior at all stages of the teaching staff to systematically monitor and take into account the dynamics of changes in personality and behavior of students.